Theoretical substantiation of the optimal parameters and shape of the working parts of a spring soil leveler - Sobolevsky I.V.; Kuklin V.A.; Kalafatov I.I.; Kanevskaya A.A. (E3S Web of Conferences, 2024)
The article presents a theoretical justification for the optimal parameters and shape of the working parts of a spring soil leveler. For this purpose, an effective design scheme for a spring soil leveler was developed. A curved bar consisting of three working surfaces with a toothed comb in the lower part is proposed as a working body of the spring equalizer. Taking into account the physical and mechanical properties of the soils of the Republic of Crimea and the agrotechnical requirements for erosion control treatment, the angles α, β, γ and the dimensions of the compacting-cutting part AB, the leveling part BC and the limiting part CD of the leveling bar of the elastic soil leveler are justified. A theoretical dependence was obtained to determine the required value of the damper stiffness coefficient kd. The range of adjustment of the angle of the leveling bar varies from 15 to 35 degrees. The length of the leveling bars also varies in the range from 140 to 200 mm. The technological train of the developed spring leveler will form a leveled surface and form a ribbed soil microrelief resistant to wind erosion.